2002
DOI: 10.1046/j.1365-2958.2002.03127.x
|View full text |Cite
|
Sign up to set email alerts
|

A locus of group A streptococcus involved in invasive disease and DNA transfer

Abstract: SummaryGroup A streptococcus (GAS) causes diseases ranging from benign to severe infections such as necrotizing fasciitis (NF). The reasons for the differences in severity of streptococcal infections are unexplained. We developed the polymorphic-tag-lengthstransposon-mutagenesis (PTTM) method to identify virulence genes in vivo . We applied PTTM on an emm 14 strain isolated from a patient with NF and screened for mutants of decreased virulence, using a mouse model of human soft-tissue infection. A mutant that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
165
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(168 citation statements)
references
References 50 publications
(79 reference statements)
2
165
1
Order By: Relevance
“…inoculation with serotypes causing invasive GAS diseases in human (13,21,24,25,29,30,43,44). Studies based on the above-mentioned murine models demonstrated that PMNs constitute an essential defense component preventing the transition of GAS from local to disseminated infection and, hence, GAS produces a plethora of virulence factors that hamper PMN responses (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…inoculation with serotypes causing invasive GAS diseases in human (13,21,24,25,29,30,43,44). Studies based on the above-mentioned murine models demonstrated that PMNs constitute an essential defense component preventing the transition of GAS from local to disseminated infection and, hence, GAS produces a plethora of virulence factors that hamper PMN responses (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were conducted using GAS strains JS95 of the M14 serotype (21) and 5448 of the M1T1 serotype (22) GAS strains were cultured in Todd-Hewitt medium supplemented with 0.2% yeast extract (Difco, BD Diagnostics) or on blood agar plates (Novamed, Jerusalem, Israel).…”
Section: Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Hidalgo-Grass et al identified the streptococcal invasion locus (sil) using the polymorphic tag-length transposon mutagenesis (PTTM) method on JS95, an emm14 GAS strain isolated from a patient with NF (13). In this strain, the sil locus was shown to control GAS spread into deeper tissues in a mouse model of human soft tissue infection and to be involved in DNA transfer between two emm14 strains (13).…”
mentioning
confidence: 99%